Polymers in biosensors - Long, Jia Jia; Benoudjit, Abdel Mohsen; Arris, Farrah Aida; Ali, Fathilah; Wan Salim, Wan Wardatul Amani (Springer Nature, 2018)
Polymers can be conductive or nonconductive, natural or synthetic, and have been widely used in the development of biosensors; polymers can be processed at a large scale at a relatively low cost. Poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), PANI, and PPy are widely used in fabricating biosensors owing to their intrinsic conductive property. Although conductivity is crucial in developing biosensors, a large number of nonconductive polymers such as chitin, chitosan, gelatin, dextran, cellulose, and polystyrene also attract interest for their function as support matrices for the immobilization of biomolecules. The non- conductive polymers can be classified into two categories: natural and synthetic. This chapter focuses on the potential use of polymer composites in biosensors.